Problems of choosing column foundation structures according to labor consumption and productivity of their arrangement - NOSACH, Kateryna (Ways to Improve Construction Efficiency, 2024)
Reinforced concrete frame structures are often used in construction practice due to a successful combination of the characteristics of the cost and duration of construction work, as well as the versatility of the purpose of ready-made buildings. The construction industry strives to combine such areas of development as speeding up building construction, reducing labor-intensive processes and lowering the cost of work and materials - without losing the quality characteristics of the finished building. In order to achieve the listed properties, the development and invention of new equipment, materials and structural and technological solutions is taking place. The construction of columnar foundations takes about 15-20% of the time resource, so there is a need to find solutions that can speed up the processes and make them cheaper. The modern level of development of the construction industry allows the use of various structures and equipment, as well as combining technological solutions for the arrangement of structures and individual elements, in particular columnar foundations. A popular solution is the installation of prefabricated monolithic foundations, which, in its finished form, should combine the advantages of prefabricated and monolithic technologies. The possibility of combining modern solutions and technologies requires research to determine the expediency and effectiveness of constructive solutions, as well as to determine the algorithm of actions. The question arises about the prospects of modern methods. This article provides an overview of the existing solutions that can be used for the installation of prefabricated monolithic foundations, taking into account the structural requirements in accordance with current regulations. The main advantages and disadvantages of each of the solutions, as well as the conditions of application, are determined. Methods of using modern prefabricated structures, equipment, as well as the combination of technology of prefabricated monolithic foundations are considered in order to find options that meet the needs. It was determined that there is not enough analytical and empirical data regarding the effectiveness of the adopted decisions in interaction with the rest of the factors, such as structural and technological solutions of the remaining elements of the building, volume-planning solutions, conditions of the construction site, environmental conditions.